A new potential intervention strategy to promote the “body-mind-brain” health development of Chinese children and adolescents: a scoping review - Long Jin; Kai Qi; Zehao Zhang; Jia Yang; Yifan Shi; Aiguo Chen (Frontiers in Sports and Active Living, 2026)
Objective This scoping review maps the extent and nature of literature on Shaolin martial arts (SMA) and examines how direct, contextual, and indirect evidence may inform hypotheses about body-mind-brain health in children and adolescents. It does not evaluate intervention effectiveness. Methods Following PRISMA-ScR guidance, we searched PubMed, Web of Science, CNKI, and Wanfang Data from database inception to February 2026. Eligibility was defined by the population-concept-context framework. Records were classified as direct empirical evidence, contextual SMA literature, or indirect mechanistic evidence from related practices. Classical Chinese sources were used only to describe SMA principles and cultural context, not as evidence of health outcomes. Results Twelve of the 13 included sources were contextual publications on SMA history, philosophy, education, or dissemination, and only one examined Shaolin boxing in children aged 8–10 years. The broader literature on martial arts, tai chi, qigong, meditation, and physical activity provides only indirect support for proposed physical, psychological, and cognitive mechanisms. No direct evidence currently establishes that SMA reduces anxiety or depression, improves executive function, alters brain activation, or induces neuroplasticity in children and adolescents. Conclusion The current literature supports SMA as a culturally grounded candidate for future intervention development, but not as an empirically validated health intervention for children and adolescents. Feasibility studies and well-designed controlled trials with standardized SMA protocols and prespecified physical, mental-health, cognitive, and neurobiological outcomes are required before effectiveness claims can be made.